IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI DALAM KURIKULUM MERDEKA:STUDI KASUS GURU SD DI KELAS HETEROGEN DI SD N 26 PEMECUTAN - Sagung Wulan Prami Ningrat, A.A; Anak Agung Ngurah Budiadnyana; Ni Nyoman Ayu Suciartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the planning, implementation, assessment, challenges, and impacts of differentiated learning implementation at SD N 26 Pemecutan. This study used a qualitative approach with a case study research type. Data collection techniques were carried out through observation, interviews, and documentation. This study applied the theories of student-centered learning, constructivism theory, individual differences theory, assessment for learning, behavioristic theory, and social learning theory as the basis for research analysis. The data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that differentiated learning was implemented through adjustments to learning content, processes, and assessments according to students’ abilities. Teachers used strategies such as small group learning, scaffolding, peer tutoring, and various learning media. The challenges faced included time management, students’ learning readiness, and limited facilities. However, teachers made various efforts such as personal approaches, learning reflection, and flexible learning strategies. The implementation of differentiated learning had a positive impact on students’ activeness, self-confidence, and learning comprehension in heterogeneous classrooms.